Promoting bone callus formation by taking advantage of the time-dependent fracture gap strain modulation - Wähnert, Dirk; Miersbach, Marco; Colcuc, Christian; Brianza, Stefano; Vordemvenne, Thomas; Plecko, Michael; Schwarz, Angelika (Frontiers in Surgery, 2024)
Delayed union and non-union of fractures continue to be a major problem in trauma and orthopedic surgery. These cases are challenging for the surgeon. In addition, patients suffer from multiple surgeries, pain and disability. Furthermore, these cases are a major burden on healthcare systems. The scientific community widely agrees that the stability of fixation plays a crucial role in determining the outcome of osteosynthesis. The extent of stabilization affects factors like fracture gap strain and fluid flow, which, in turn, influence the regenerative processes positively or negatively. Nonetheless, a growing body of literature suggests that during the fracture healing process, there exists a critical time frame where intervention can stimulate the bone's return to its original form and function. This article provides a summary of existing evidence in the literature regarding the impact of different levels of fixation stability on the strain experienced by newly forming tissues. We will also discuss the timing and nature of this 'window of opportunity' and explore how current knowledge is driving the development of new technologies with design enhancements rooted in mechanobiological principles.